Flow State While Using Mixed Reality to Create Episodic Digital Experiences - Karnchanapayap, Gomesh; Ang, Kevin (DEC Journal : Art and Design, 2024)
This study investigates the intersection of flow states and Mixed Reality (MR) technology within artistic creation and immersive storytelling, emphasizing the transformative potential of MR tools in enhancing creativity, collaboration, and engagement. By integrating MR into artistic workflows, the research highlights how adaptability and perseverance in navigating advanced technologies can drive innovative practices, offering valuable insights for artists, designers, and technologists. The primary objective of this research is to explore how MR art authoring tools can facilitate flow states in creative processes and enable the creation of episodic extended reality (XR) experiences that seamlessly merge digital and physical realities. A qualitative methodology was employed, centered on collaborative artistic experiments conducted during an artist residency at Silpakorn University’s Faculty of Decorative Arts. Participants included an experienced XR artist, Master’s and Ph.D. student, and faculty members. Workshops, seminars, and real-world applications of MR tools—such as Gravity Sketch, Open Brush, Nomad Sculpt, and Adobe Aero—provided a platform to analyze the dynamics of flow states in MR environments. The findings reveal that MR tools effectively induce flow states, characterized by time distortion, fulfillment, and autotelic behavior. Episodic XR storytelling emerged as a compelling medium for immersive artistic expression, with characters like Jaffa the biscuit maker and Juju the little pig exemplifying the imaginative possibilities of MR technology. Participants demonstrated heightened engagement, collaboration, and adaptability, overcoming technological challenges while reimagining physical spaces through geospatially anchored augmented reality (AR) experiences. The study underscores the importance of maintaining a flexible and experimental mindset to navigate the complexities of emerging technologies. It highlights the synergistic relationship between flow psychology and MR tools, emphasizing the critical role of play in unlocking creativity and fostering genuine self-expression. The collaborative and iterative processes observed affirm MR’s potential to inspire dynamic narratives, transform artistic workflows, and contribute to the evolving understanding of flow states and digital creativity in contemporary art practice of storytelling that emphasizes the impact that technology has on the production of immersive media.